LOCAL OSCILLATORS FOR MM-WAVELENGTH AERONOMIC RECEIVERS - Myshenko, V. V.; Shulga, V. M.; Korolev, A. M.; Karelin, Yu. V.; Chechotkin, D. L.; Antyufeyev, O. V.; Patoka, O. M. (Видавничий дім «Академперіодика», 2019)
PACS numbers: 95.85.Bh,97.10.Bt, 98.38.Ez Purpose: A description of the original technical solutions of the solid-state highly stable local oscillators of the millimeter range and the results of the study of the main characteristics of the developed devices are given. The goal of the work is the development of small-sized stabilized generators with low power consumption for the use in the composition of superheterodyne receivers of the 2 mm and 3 mm ranges for aeronomic research.Design/methodology/approach: The created local oscillators are based on multiple multiplication of the reference signal with a phase locked loop. The output generator on the Gunn diode works without a varactor, with the frequency tuning by changing the voltage on the diode. To measure the spectral characteristics, a test signal of a separate highly stable heterodyne of an astronomical receiver was used. The spectrum of the investigated local oscillator was recorded by a parallel Fourier spectrum analyzer with the frequency resolution of 1 kHz per channel. Methods for the study of other basic characteristics were standard methods of radio measurements.Findings: Compact sources of the heterodyne signal of the mm-wavelength range with low power consumption (less than 20 W) were designed and tested. The output power of the local oscillators is at least 50 mW. The measured relative frequency instability is better than 10-8 when working with a thermostatted quartz reference source. The time resource of continuous work exceeds 2 years.Conclusions: Relative instability of frequency (10-8 ) and launch power (more than 50 mW) of the presented generators correspond to the characteristics of industrial mm-wavelength precision generators, the here developed generators (devices) being more economical, compact and cheaper. A number of proposed circuit and design solutions can be used by designers of similar equipment in the mm-wavelength range.Key words: millimeter waves, local oscillator, economy, stability, phase locked loopManuscript submitted  11.04.2019Radio phys. radio astron. 2019, 24(2): 144-153REFERENCES1. HOFFMANN, C. G., RAFFALSKI, U., PALM M., FUNKE, B., GOLCHERT, S. H. W., HOCHSCHILD, G. and NOTHOLT, J., 2011. Observation of strato-mesospheric CO above Kiruna with ground-based microwave radiometry – retrieval and satellite comparison. Atmos. Meas. Tech. vol. 4, is. 11, pp. 2389–2408. DOI: https://doi.org/10.5194/amt-4-2389-20112. STRAUB, C., ESPY, P. J., HIBBINS, R. E. and NEWNHAM, D. A., 2013. Mesospheric CO above Troll station, Antarctica observed by a ground based microwave radiometer. Earth Syst. Sci. Data. vol. 5, is. 1, pp. 199–208. DOI: https://doi.org/10.5194/essd-5-199-20133. HAGEN, J., MURK, A., RÜFENACHT, R., KHAYKIN, S., HAUCHECORNE, A. and KÄMPFER, N., 2018. WIRA-C: a compact 142-GHz-radiometer for continuous middle-atmospheric wind measurements. Atmos. Meas. Tech. vol. 11, is. 9, pp. 5007–5024. DOI: https://doi.org/10.5194/amt-11-5007-20184. RÜFENACHT, R., KÄMPFER, N. and MURK, A., 2012. First middle-atmospheric zonal wind profile measurements with a new ground-based microwave Doppler-spectro-radiometer. Atmos. Meas. Tech. vol. 5, is. 11, pp. 2647–2659. DOI: https://doi.org/10.5194/amt-5-2647-20125. ANTYUFEYEV, A. V. and SHULGA, V. M., 2005. FFT-based digital spectrum analyzer on PC. Radiotekhnika. no. 10. pp. 145–148. (in Russian).6. KARELIN, YU. V., ANTYUFEYEV, O. V., MYSHEN KO, V. V. and SHULGA, V. M., 2017. An FPGA-based fourier FFTS-160 spectrometer for atmospheric molecular radiation  research. Telecomm. Radio Eng. vol. 76, is. 4, pp. 305–313. DOI: https://doi.org/10.1615/TelecomRadEng.v76.i4.307. FORKMAN, P., PIDDYACHIY, V., KOROLEV, A., MYSHENKO, V., MYSHENKO, A. and SHULGA, V., 2006. An uncooled very low noise Schottky diode receiver frontend for middle atmospheric ozone and carbon monoxide measurements. Int. J. Infrared Millimeter Waves. vol. 27, is. 1, pp. 25–35. DOI: https://doi.org/10.1007/s10762-006-9061-38. PIDDYACHIY, V. I., SHULGA, V. M., MYSHENKO, V. V., KOROLEV, A. M., MYSHENKO, A. V., ANTYUFEYEV, A. V., POLADICH, A. V. and SHKODIN, V. I., 2010. 3-mm wave spectroradiometer for studies of atmospheric trace gases. Radiophys. Quantum El. vol. 53, is. 5-6, pp. 326–333. DOI: https://doi.org/10.1007/s11141-010-9231-y9. PIDDYACHIY, V., SHULGA, V., MYSHENKO, V., KOROLEV, A., ANTYFEYEV, O., SHULGA, D. and FORKMAN, P., 2017. Microwave radiometer for spectral observations of mesospheric carbon monoxide at 115 GHz over Kharkiv, Ukraine. J. Infrared Millim. Terahertz Waves. vol. 38, is. 3, pp. 292–302. DOI: https://doi.org/10.1007/s10762-016-0334-110. PIDDYACHIY, V. I., KOROLEV, A. M., MYSHENKO, V. V. and SHULGA, V. M., 2015. The 2-mm range receiving module for observations of atmospheric ozone emission line at 142.2 GHz. Radio Phys. Radio Astron. vol. 20, is 3, pp. 261–268. (in Russian). DOI: https://doi.org/10.15407/rpra20.03.26111. PIDDYACHIY, V., 2015. Schottky diode tripler in the 3-mm wave receiver for investigation of atmospheric gases. Radio Phys. Radio Astron. vol. 20, is. 1, pp. 86–93. (in Russian). DOI: https://doi.org/10.15407/rpra20.01.08612. ALEKSEEV, E. A. and ZAKHARENKO, V. V., 2007. Direct Digital Synthesizer at the Microwave Spectroscopy. Radio Phys. Radio Astron. vol. 12, is. 2, pp. 205–213. (in Russian).13. ALEKSEEV, E. A., ILYUSHIN, V. V. and MESCHERYAKOV, A. A., 2014. High-precision microwave spectrometer with sub-Doppler spectral resolution. Radio Phys. Radio Astron. vol. 19, is. 4, pp. 364–374. (in Russian).DOI: https://doi.org/10.15407/rpra19.04.36414. KOROLEV, A., 2011. An Intermediate-Frequency Amplifier for a Radio-Astronomy Superheterodyne Receiver. Instrum. Exp. Tech. vol. 54, is. 1, pp. 81–83. DOI: https://doi.org/10.1134/S002044121006103X15. KOROLEV, A. M. and SHULGA, V. M., 2011. Unsaturated regime as alternative method to provide stability of low-noise amplifier on high-electron-mobility transistors. Radio Phys. Radio Astron. vol. 16, is. 4, pp. 433–439. (in Russian).16. ANTYUFEYEV, A. V., MYSHENKO, A. V. and MYSHENKO, V. V., 2013. Microwave oscillator’s spectral observation with a radio astronomy receiver. In: Proceedings of the 23-th International Crimean conference “Microwave and Telecommunication technology” (CriMiCo’2013). Sevastopol, Ukraine: IEEE, pp. 949–950